2017
DOI: 10.18410/jebmh/2017/567
|View full text |Cite
|
Sign up to set email alerts
|

Study on Diagnostic Modalities in Smear Negative Pulmonary Tuberculosis With Special Reference to Sputum Induction (Si Cbnaat), Bronchoscopy (Bal Cbnaat and Bal Culture)

Abstract: BACKGROUND Tuberculosis, an important preventable and treatable cause of death is a major health problem worldwide. However, in patients with a compatible clinical picture, sputum smear don't reveal acid-fast bacilli in all patients. So, alternative methods of obtaining sputum specimen are frequently needed in these patients. Rapid diagnosis of tuberculosis and detection of rifampicin (RIF) resistance are essential for effective disease management. CBNAAT (cartridge based nucleic acid amplification test) (DS S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
2
1
0
Order By: Relevance
“…In a study conducted by Mohanty T et al 12 shows out of 71 patients who were smear AFB-negative cases, sputum for CBNAAT was positive in 23 (32%) patients, which correlates with our study, out of 80 sputum AFB-negative samples 29 (36%) were CBNAAT positive and rest were negative. Incidence was more in diabetics, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…In a study conducted by Mohanty T et al 12 shows out of 71 patients who were smear AFB-negative cases, sputum for CBNAAT was positive in 23 (32%) patients, which correlates with our study, out of 80 sputum AFB-negative samples 29 (36%) were CBNAAT positive and rest were negative. Incidence was more in diabetics, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…In this study sensitivity of CBNAAT varied significantly between 100% in sputum smear-positive PTB and 22.6% in sputum smear negative PTB. Saugat et al 8 and Mohanty T et al 9 .,reported sensitivity of 15% and 32% of CBNAAT in smear negative PTB, which correlates with the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Sharma (New Delhi, India) described that Xpert has 77.7% sensitivity for smear negative and culture positive TB in comparison to 99.2% for smear and culture positive TB [28]. In the study of Mohanty (Cuttack, India)(April 2016 to March 2017), with culture as gold standard, sensitivity, specificity, positive predictive value(PPV) and negative predictive value(NPV) of sputum induction CBNAAT were 61.9%, 96.5%, 96.3%, 63.6%, respectively and of BAL CBNAAT were 88.09%, 96.5%, 97.36%, 84.84%, respectively [29]. Agrawal (Delhi, India, Jan 2015 to Nov 2015) demonstrated that using culture as reference, sensitivity, specificity, PPV and NPV of CBNAAT were 86.8%, 93.1%, 78.5% and 96% respectively [19].…”
Section: Discussionmentioning
confidence: 99%